Big and bendable [flexible plastic-based circuits]. - Chalamala, B.R (IEEE spectrum)
This paper discusses the possibility of cheap and fast fabrication of high-quality, even custom, plastic-based flexible integrated circuits with the aid of the low-cost technologies of inkjet printing. An important advantage of the inkjet print process over conventional techniques is that the jet process puts the circuit material only where it is needed, whereas the conventional process puts the material down over the whole substrate and then etches most of it away. By eliminating the high-temperature, high-vacuum steps used in conventional circuit manufacture, the jet process has the potential to substantially cut the manufacturing cost.